Pengaruh Literasi Ekonomi dan Persepsi Konsumen terhadap Perilaku Konsumtif Siswa SMA Negeri di Kabupaten Madiun: Penelitian - Hestin Nanda Wideaningputri; Eka Hendi Andriansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of economic literacy and consumer perception on consumer behavior of high school students in Madiun Regency. This study involved 215 respondents from 10 high schools in Madiun Regency, especially grade XI students of economics courses. Data collection was carried out through questionnaires distributed using Google Forms, while data analysis was carried out with the help of Statistical Package For The Social Sciences (SPSS) software. The results of this study indicate that economic literacy has a positive and significant effect on student consumer behavior, while consumer perception has a negative and significant effect on student consumer behavior.